Rhythm of textures in ink and wash painting - Tee, Merissa, Hui Shi (2016)
Ink and wash painting requires sensitivity and control. Each drop of water or ink and every movement of the brush on the surface of the paper determines the outcome. However, every painting is ultimately unique as it is an art form that embraces the unpredictability of these elements working together.